Lithium mineral-free heat-resistant ceramic clay and preparation method thereof
Through the formulation of ceramic material without lithium minerals and the use of special admixtures, the problems of differences in expansion coefficient and insufficient strength of ceramic materials caused by spodumene are solved, and the thermal stability and flexural strength of ceramic materials are improved.
Patent Information
- Application Number
- CN202411789656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing heat-resistant ceramic materials contain spodumene, which has a large difference in their expansion coefficient from other crystals and glass phases, which are prone to grain boundary stress, resulting in microcracks and insufficient strength.
The ceramic material formula without lithium minerals, including kaolin, alumina, titanium dioxide, quartz, potassium feldspar, magnesium oxide and special admixtures, generate cordierite with low expansion characteristics through solid phase reaction, and use silicon gel powder and epoxidized modified calcium carbonate to prepare admixtures to increase the thermal stability and flexural strength of the material.
It effectively reduces the thermal expansion coefficient of ceramic materials, reduces grain boundary stress, improves the thermal stability and flexural strength of the material, and achieves the improvement of high-temperature stability and mechanical properties of ceramics.
Smart Images

Figure BDA0005175007300000091 
Figure BDA0005175007300000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a heat-resistant ceramic mud free of lithium minerals and a preparation method thereof. Background Art
[0002] Clay ceramic cookware is the earliest cookware produced and used in human society. Its historical development continues to this day. Cooking and stewing food with ceramic heat-resistant pots is still an important choice for domestic and foreign catering cookware. The chemical composition, mineral composition and physical properties of the heat-resistant ceramic materials that make up the pot body are different from those of ordinary ceramics made of kaolin-feldspar-quartz. The microcrystalline structure of heat-resistant ceramic materials consists of three parts: crystal phase, glass phase and pores. Heat-resistant ceramic products should have good thermal shock resistance and high tensile strength. There are three ways to improve the thermal shock resistance of ceramic materials: one is to increase the reasonable porosity of the product and use microscopic gaps to absorb the stress generated by the heating and expansion of the product; the second is to increase the thermal conductivity, such as introducing clinkers with high thermal conductivity such as corundum and silicon carbide; the third is to reduce the expansion coefficient of the material, fundamentally eliminating the destructive stress generated by the rapid cooling and heating of the cookware. In summary, reducing the expansion coefficient of ceramic materials is an effective way to improve the thermal stability of ceramic heat-resistant pots.
[0003] The existing formula of heat-resistant ceramic materials often uses spodumene as the main raw material, and its crystal phase is mainly β-spodumene and its solid solution, mullite and residual quartz. Adding spodumene in the preparation process of heat-resistant ceramic materials makes the product have good thermal shock resistance and fluxing properties, which can effectively reduce the thermal expansion coefficient and sintering temperature of the product, shorten the sintering time, and improve its high-temperature fluidity viscosity. The chemical formula of spodumene is Li2O-Al2O3-4S i O2, the theoretical Li2O content is 8.03%, and spodumene concentrate generally contains 6.3-7.5% Li2O. The chemical activity of Li2O in spodumene is stronger than that of K2O and Na2O, and the fluxing effect is much stronger than that of K2O and Na2O. In the traditional kaolinite-feldspar-quartz ceramic system, quartz rarely participates in the reaction at a temperature of 1200°C, but after adding 30-80% spodumene, quartz has reacted at a temperature of 1100°C. Li2O has the following effects on SiO2: (1) It causes quartz to continuously dissolve in the melt, inhibiting the conversion of residual quartz to cristobalite with a high thermal expansion coefficient; (2) It reduces the temperature of the transformation from β-quartz to α-quartz crystal type; (3) It has a strong crystallization ability, and the melt lattice absorbs SiO2, effectively avoiding the problem of cristobalite in the material due to excessive SiO2. The thermal expansion coefficient of the heat-resistant ceramic material obtained by adding spodumene instead of feldspar as the solvent of the blank can be less than 2×10 -6 / ℃ (20-800℃). However, due to the scarcity of spodumene resources in my country and the fact that spodumene undergoes crystal transformation at high temperatures, it needs to be calcined before use, which increases the production cost of heat-resistant ceramic materials. In addition, the expansion coefficient of spodumene crystals is very different from that of other crystals and glass phases, which easily generates grain boundary stress and causes microcracks, which in turn leads to insufficient strength of lithium aluminum silicon ceramic materials. Summary of the invention
[0004] The purpose of the present invention is to provide a heat-resistant ceramic mud without lithium minerals and a preparation method thereof, so as to solve the following technical problems:
[0005] Existing heat-resistant ceramic materials use spodumene as the main raw material. The expansion coefficient of spodumene crystals is very different from that of other crystals and glass phases, which easily produces grain boundary stress and causes microcracks, thereby resulting in insufficient strength of lithium aluminum silicon ceramic materials.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing heat-resistant ceramic mud without lithium minerals comprises the following steps:
[0008] S1: Blending kaolin, alumina, titanium dioxide, quartz, potassium feldspar and magnesium oxide according to the weight ratio of the raw materials to obtain a dry material;
[0009] S2: Mixing the admixture with water, and then with dry materials, and kneading the mud to obtain heat-resistant ceramic mud;
[0010] The preparation method of the admixture comprises the following steps:
[0011] A1: Add γ-mercaptopropyltriethoxysilane, tetraethyl orthosilicate, p-toluenesulfonic acid and anhydrous ethanol into a reaction kettle and disperse them evenly, stir them magnetically for 6-9 hours, dry and crush them to obtain silica gel powder;
[0012] A2: In a nitrogen atmosphere, add silica gel powder, vinyl phosphoric acid and anhydrous ethanol into a reaction kettle, control the temperature at 40-50°C, keep the reaction warm for 6-9 hours, and remove the ethanol by rotary evaporation to obtain component 1;
[0013] A3: Add component 1, epoxidized modified calcium carbonate and deionized water into a reaction kettle and disperse them evenly. Control the temperature at 50-60°C, keep the reaction warm for 3-6 hours, and dry to obtain an admixture.
[0014] As a further solution of the present invention: the heat-resistant ceramic mud comprises the following raw materials in parts by weight: 22-30 parts of kaolin, 20-25 parts of alumina, 15-21 parts of titanium dioxide, 10-15 parts of quartz, 5-8 parts of potassium feldspar, 6-8 parts of magnesium oxide, and 5-10 parts of additives.
[0015] As a further embodiment of the present invention: in step A1, the addition ratio of γ-mercaptopropyltriethoxysilane, tetraethyl orthosilicate, p-toluenesulfonic acid and anhydrous ethanol is 1-2 g: 10 g: 0.05-0.1 g: 15-25 mL.
[0016] As a further solution of the present invention: in step A2, the addition ratio of the silica gel powder, vinyl phosphoric acid and anhydrous ethanol is 10 g: 0.5-1 g: 50-100 mL.
[0017] As a further solution of the present invention: in step A3, the addition ratio of component 1, epoxidized modified calcium carbonate, and deionized water is 10 g: 2-4 g: 10-20 mL.
[0018] As a further embodiment of the present invention: the preparation method of epoxidized modified calcium carbonate comprises the following steps:
[0019] Add nano calcium carbonate, deionized water and anhydrous ethanol into a reaction kettle and disperse them evenly, add γ-glycidyloxypropyltrimethoxysilane, control the temperature at 50-60°C, keep the reaction warm for 3-6 hours, wash with ethanol, and dry to obtain epoxidized modified calcium carbonate.
[0020] As a further solution of the present invention: the addition ratio of nano calcium carbonate, deionized water, anhydrous ethanol and γ-glycidyloxypropyltrimethoxysilane is 10g:50-100mL:50-100mL:1-3g.
[0021] As a further solution of the present invention: kaolin is obtained by mixing kaolin powder with a particle size of 5-10 um and kaolin powder with a particle size of 10-25 um in a mass ratio of 1:2-4.
[0022] As a further solution of the present invention: alumina, titanium dioxide, quartz, potassium feldspar and magnesium oxide are all sieved through a 100-250 mesh standard sieve.
[0023] A heat-resistant ceramic mud containing no lithium minerals, prepared by any one of the above-mentioned preparation methods.
[0024] Beneficial effects of the present invention:
[0025] The present invention uses kaolin, alumina, titanium dioxide, quartz, potassium feldspar, magnesium oxide and additives as raw materials to prepare ceramic mud; wherein, aluminum titanate solid solution is synthesized by solid phase reaction of alumina and titanium dioxide, which has the properties of low expansion and high melting point, but has the characteristics of low strength due to micro cracking; magnesium oxide is added to the components of the present invention, Mg 2+ Substituting Al in aluminum titanate 3+Magnesium titanate is produced, and magnesium titanate and aluminum titanate form a continuous solid solution, which greatly reduces the degree of distortion of the octahedron in the aluminum titanate crystal structure and improves the thermal stability of the material. The present application utilizes quartz, kaolin, and potassium feldspar to undergo a solid-phase reaction to generate cordierite with low expansion characteristics. The fine cordierite is evenly dispersed between the various items, effectively regulating the various solid phases with large thermal expansion differences, playing a transitional role between the solid solution, mullite, and glass phases, alleviating the grain boundary stress caused by the large thermal expansion differences of the various items, and avoiding or reducing the generation of cracks.
[0026] The present application uses tetraethyl orthosilicate and mercaptosilane coupling agent as precursors, p-toluenesulfonic acid as a catalyst, adopts sol-gel reaction, and controls the hydrolysis polymerization process to prepare silica gel powder; and uses the mercapto group of the silica gel powder to undergo a click reaction with vinyl phosphate to graft phosphoric acid groups on the organic molecular chain of the material to obtain component one; the present application then uses the phosphoric acid group of component one to undergo a ring-opening reaction with the epoxy group of epoxidized modified calcium carbonate to obtain an additive.
[0027] The admixture prepared in the present application is added to the ceramic mud. After the admixture is decomposed, highly active silicon dioxide is formed. At about 1100°C, the free silicon dioxide enters the lattice, the thermal expansion anisotropy of the material increases, and the thermal expansion coefficient tends to decrease, which promotes the formation of ceramic bonding and improves the compressive strength of the material. Due to the presence of phosphate groups and calcium elements in the admixture of the present application, the gas produced after its decomposition not only effectively increases the amount of closed pores in the material, but also maintains the integrity of the pores, which is beneficial to improve the thermal shock resistance. The microcrystals produced during the sintering process of the admixture are compounded with the glass phase of the ceramic, which significantly improves the strength and toughness of the ceramic material. The ceramic material prepared in the present application has the characteristics of good thermal shock resistance. The material can withstand hot and cold shocks from 700°C to 20°C and remain intact. DETAILED DESCRIPTION
[0028] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1 The preparation method of epoxidized modified calcium carbonate comprises the following steps:
[0030] 10 g of nano calcium carbonate, 50 mL of deionized water and 50 mL of anhydrous ethanol were added into a reaction kettle and dispersed evenly. 3 g of γ-glycidyloxypropyltrimethoxysilane was added. The temperature was controlled at 50° C. and the reaction was kept warm for 6 hours. The mixture was washed with ethanol and dried to obtain epoxidized modified calcium carbonate.
[0031] The preparation method of the admixture of embodiment 2 comprises the following steps:
[0032] A1: 2 g of γ-mercaptopropyltriethoxysilane, 20 g of tetraethyl orthosilicate, 0.1 g of p-toluenesulfonic acid and 30 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly, magnetically stirred for 6 h, dried and crushed to obtain silica gel powder;
[0033] A2: In a nitrogen atmosphere, 10 g of silica gel powder, 0.5 g of vinyl phosphoric acid, and 50 mL of anhydrous ethanol were added to a reaction kettle, the temperature was controlled at 40°C, the reaction was kept warm for 6 hours, and the ethanol was removed by rotary evaporation to obtain component 1;
[0034] A3: Add 10 g of component 1, 2 g of the epoxidized modified calcium carbonate prepared in Example 1, and 10 mL of deionized water into a reaction kettle and disperse them evenly. Control the temperature at 50° C., keep the reaction warm for 3 h, and dry to obtain an admixture.
[0035] The preparation method of the additive of embodiment 3 comprises the following steps:
[0036] A1: 3 g of γ-mercaptopropyltriethoxysilane, 20 g of tetraethyl orthosilicate, 0.15 g of p-toluenesulfonic acid and 40 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly, magnetically stirred for 6 h, dried and crushed to obtain silica gel powder;
[0037] A2: In a nitrogen atmosphere, 10 g of silica gel powder, 0.7 g of vinyl phosphoric acid, and 50 mL of anhydrous ethanol were added to a reaction kettle, the temperature was controlled at 45°C, and the reaction was kept warm for 6 hours. The ethanol was removed by rotary evaporation to obtain component 1;
[0038] A3: Add 10 g of component 1, 3 g of epoxidized modified calcium carbonate prepared in Example 1 and 10 mL of deionized water into a reaction kettle and disperse them evenly. Control the temperature at 55° C., keep the reaction warm for 3-6 hours, and dry to obtain an admixture.
[0039] The preparation method of the additive of embodiment 4 comprises the following steps:
[0040] A1: 4 g of γ-mercaptopropyltriethoxysilane, 20 g of tetraethyl orthosilicate, 0.2 g of p-toluenesulfonic acid and 50 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly, magnetically stirred for 9 h, dried and crushed to obtain silica gel powder;
[0041] A2: In a nitrogen atmosphere, 10 g of silica gel powder, 1 g of vinyl phosphoric acid, and 100 mL of anhydrous ethanol were added to a reaction kettle, the temperature was controlled at 50°C, the reaction was kept warm for 9 hours, and the ethanol was removed by rotary evaporation to obtain component 1;
[0042] A3: Add 10 g of component 1, 4 g of the epoxidized modified calcium carbonate prepared in Example 1, and 20 mL of deionized water into a reaction kettle and disperse them evenly. Control the temperature at 60° C., keep the reaction warm for 6 h, and dry to obtain an admixture.
[0043] Embodiment 5 A method for preparing a heat-resistant ceramic mud free of lithium minerals comprises the following steps:
[0044] S1: kaolin powder with a particle size of 5-10 um and kaolin powder with a particle size of 10-25 um are mixed in a mass ratio of 1:2 to obtain kaolin;
[0045] S2: Blend 250 g of kaolin, 240 g of aluminum oxide (passed through a 250-mesh standard sieve), 200 g of titanium dioxide (passed through a 250-mesh standard sieve), 120 g of quartz (passed through a 250-mesh standard sieve), 50 g of potassium feldspar (passed through a 250-mesh standard sieve), and 80 g of magnesium oxide (passed through a 250-mesh standard sieve) to obtain a dry material;
[0046] S3: 60 g of the admixture prepared in Example 2 was mixed with 700 mL of water, and then mixed with 940 g of dry materials, and kneaded to obtain heat-resistant ceramic mud.
[0047] Embodiment 6 A method for preparing a heat-resistant ceramic mud free of lithium minerals comprises the following steps:
[0048] S1: kaolin powder with a particle size of 5-10 um and kaolin powder with a particle size of 10-25 um are mixed in a mass ratio of 1:2 to obtain kaolin;
[0049] S2: Blend 250 g of kaolin, 240 g of aluminum oxide (passed through a 250-mesh standard sieve), 200 g of titanium dioxide (passed through a 250-mesh standard sieve), 120 g of quartz (passed through a 250-mesh standard sieve), 50 g of potassium feldspar (passed through a 250-mesh standard sieve), and 80 g of magnesium oxide (passed through a 250-mesh standard sieve) to obtain a dry material;
[0050] S3: 60 g of the admixture prepared in Example 3 was mixed with 700 mL of water, and then mixed with 940 g of dry materials, and kneaded to obtain heat-resistant ceramic mud.
[0051] Embodiment 7 A method for preparing a heat-resistant ceramic mud free of lithium minerals comprises the following steps:
[0052] S1: kaolin powder with a particle size of 5-10 um and kaolin powder with a particle size of 10-25 um are mixed in a mass ratio of 1:2 to obtain kaolin;
[0053] S2: Blend 250 g of kaolin, 240 g of aluminum oxide (passed through a 250-mesh standard sieve), 200 g of titanium dioxide (passed through a 250-mesh standard sieve), 120 g of quartz (passed through a 250-mesh standard sieve), 50 g of potassium feldspar (passed through a 250-mesh standard sieve), and 80 g of magnesium oxide (passed through a 250-mesh standard sieve) to obtain a dry material;
[0054] S3: 60 g of the admixture prepared in Example 4 was mixed with 700 mL of water, and then mixed with 940 g of dry materials, and kneaded to obtain heat-resistant ceramic mud.
[0055] The preparation method of the admixture of Comparative Example 1 comprises the following steps:
[0056] 3 g of γ-mercaptopropyltriethoxysilane, 20 g of tetraethyl orthosilicate, 0.15 g of p-toluenesulfonic acid and 40 mL of anhydrous ethanol were added into a reaction kettle and dispersed evenly. The mixture was stirred magnetically for 6 h, dried and crushed to obtain an admixture.
[0057] The preparation method of the admixture of Comparative Example 2 comprises the following steps:
[0058] A1: 3 g of γ-mercaptopropyltriethoxysilane, 20 g of tetraethyl orthosilicate, 0.15 g of p-toluenesulfonic acid and 40 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly, magnetically stirred for 6 h, dried and crushed to obtain silica gel powder;
[0059] A2: In a nitrogen atmosphere, 10 g of silica gel powder, 0.7 g of vinyl phosphoric acid and 50 mL of anhydrous ethanol were added into a reactor, the temperature was controlled at 45°C, the reaction was kept warm for 6 h, and the ethanol was removed by rotary evaporation to obtain an admixture.
[0060] Comparative Example 3 The preparation method of vinyl calcium carbonate comprises the following steps:
[0061] 10 g of nano calcium carbonate, 50 mL of deionized water and 50 mL of anhydrous ethanol were added into a reaction kettle and dispersed evenly. 3 g of vinyl triethoxysilane was added. The temperature was controlled at 50°C and the reaction was kept warm for 6 hours. The reaction was then washed with ethanol and dried to obtain vinyl calcium carbonate.
[0062] The preparation method of the admixture comprises the following steps:
[0063] A1: 3 g of γ-mercaptopropyltriethoxysilane, 20 g of tetraethyl orthosilicate, 0.15 g of p-toluenesulfonic acid and 40 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly, magnetically stirred for 6 h, dried and crushed to obtain silica gel powder;
[0064] A2: Add 10g of component 1, 3g of vinyl calcium carbonate and 10mL of deionized water into a reaction kettle and disperse them evenly. Control the temperature to 55°C, keep the reaction warm for 3-6h, and dry to obtain an admixture.
[0065] Comparative Example 4 Compared with Example 6, Example 4 only replaces the admixture prepared in Example 3 and added in Example 6 with the admixture prepared in Comparative Example 1. The remaining components and preparation method of Comparative Example 4 are exactly the same as those of Example 6.
[0066] Comparative Example 5 Compared with Example 6, Example 5 only replaces the admixture prepared in Example 3 added in Example 6 with the admixture prepared in Comparative Example 2. The remaining components and preparation method of Comparative Example 5 are exactly the same as those of Example 6.
[0067] Comparative Example 6 Compared with Example 6, only the mass of the admixture prepared in Example 3 added in Example 6 is replaced by the admixture prepared in Comparative Example 3, and the remaining components and preparation method of Comparative Example 6 are exactly the same as those of Example 6.
[0068] Performance Testing
[0069] Preparation of ceramic samples:
[0070] C1: Pour the ceramic mud prepared in Examples 5-7 and Comparative Examples 4-6 into a gypsum mold respectively, let it stand for 1.5 hours to absorb the slurry, pour out the remaining mud, let it stand for another hour, demold, and dry to obtain a blank;
[0071] C2: Place the blank in a kiln and calcine it: the first calcination is carried out at a heating rate of 5°C / min, heating to 900°C; the second calcination is carried out at a heating rate of 3°C / min, heating from 900°C to 1550°C, keeping the temperature for 4h, and cooling with the furnace to obtain a ceramic sample.
[0072] (1) Thermal stability: The ceramic samples were heat exchanged at 700°C to 20°C. The test results are shown in Table 1-2.
[0073] (2) Flexural strength: Tested according to GB / T 3001-2017 Test method for flexural strength of refractory materials at room temperature. The test results are shown in Table 1-2.
[0074] (3) Water absorption: Tested according to GB / T 3299-2011 "Determination of water absorption of daily-use ceramics". The test results are shown in Table 1-2.
[0075] (4) Apparent porosity: tested according to GB / T 2997-2015 “Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products”. The test results are shown in Table 1-2.
[0076] (5) Thermal expansion coefficient: The thermal expansion coefficient of the material was tested at room temperature -600°C using the RPZ-01 thermal expansion tester. The test results are shown in Table 1-2.
[0077] Table 1: Statistical table of performance test data of Examples 5-7
[0078] Example 5 Example 6 Example 7 Thermal stability Five times without cracking Five times without cracking Five times without cracking Flexural strength / MPa 87.9 88.8 87.5 Water absorption / % 0.05 0.04 0.07 Apparent porosity / % 4.0 4.1 4.3 Thermal expansion coefficient / / ℃ <![CDATA[2.1×10 -7 ]]> <![CDATA[1.9×10 -7 ]]> <![CDATA[2.3×10 -7 ]]> Decomposition rate (1100℃×30h) / % 10.5 10.2 10.6
[0079] Table 2: Comparative Examples 4-6 Performance Test Data Statistics
[0080]
[0081]
[0082] It can be seen from Table 1-2 that the admixture prepared in the present application is added to ceramic mud, which effectively adjusts the porosity of the ceramic material, reduces the thermal expansion coefficient of the material, improves the flexural strength of the material, and achieves the thermal stability and mechanical properties of the ceramic.
[0083] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a heat-resistant ceramic mud free of lithium minerals, characterized in that: The steps include: S1: Blending kaolin, alumina, titanium dioxide, quartz, potassium feldspar and magnesium oxide according to the weight ratio of the raw materials to obtain a dry material; S2: Mixing the admixture with water, and then mixing with dry materials, and kneading the mud to obtain heat-resistant ceramic mud; The preparation method of the admixture comprises the following steps: A1: Add γ-mercaptopropyltriethoxysilane, tetraethyl orthosilicate, p-toluenesulfonic acid and anhydrous ethanol into a reaction kettle and disperse them evenly, stir them magnetically for 6-9 hours, dry and crush them to obtain silica gel powder; A2: In a nitrogen atmosphere, add silica gel powder, vinyl phosphoric acid and anhydrous ethanol into a reaction kettle, control the temperature at 40-50°C, keep the reaction warm for 6-9 hours, and remove the ethanol by rotary evaporation to obtain component 1; A3: Add component 1, epoxidized modified calcium carbonate and deionized water into a reaction kettle and disperse them evenly. Control the temperature at 50-60°C, keep the reaction warm for 3-6 hours, and dry to obtain an admixture.
2. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 1, characterized in that: The heat-resistant ceramic mud comprises the following raw materials in parts by weight: 22-30 parts of kaolin, 20-25 parts of aluminum oxide, 15-21 parts of titanium dioxide, 10-15 parts of quartz, 5-8 parts of potassium feldspar, 6-8 parts of magnesium oxide, and 5-10 parts of additives.
3. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 1, characterized in that: In step A1, the addition ratio of γ-mercaptopropyltriethoxysilane, tetraethyl orthosilicate, p-toluenesulfonic acid, and anhydrous ethanol is 1-2 g: 10 g: 0.05-0.1 g: 15-25 mL.
4. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 1, characterized in that: In step A2, the addition ratio of silica gel powder, vinyl phosphoric acid and anhydrous ethanol is 10 g: 0.5-1 g: 50-100 mL.
5. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 1, characterized in that: In step A3, the addition ratio of component 1, epoxidized modified calcium carbonate, and deionized water is 10 g: 2-4 g: 10-20 mL.
6. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 1, characterized in that: The preparation method of epoxidized modified calcium carbonate comprises the following steps: Add nano calcium carbonate, deionized water and anhydrous ethanol into a reaction kettle and disperse them evenly, add γ-glycidyloxypropyltrimethoxysilane, control the temperature at 50-60°C, keep the reaction warm for 3-6 hours, wash with ethanol, and dry to obtain epoxidized modified calcium carbonate.
7. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 6, characterized in that: The addition ratio of nano calcium carbonate, deionized water, anhydrous ethanol and γ-glycidyloxypropyltrimethoxysilane is 10g: 50-100mL: 50-100mL: 1-3g.
8. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 1, characterized in that: The kaolin is obtained by mixing kaolin powders with a particle size of 5-10 um and 10-25 um in a mass ratio of 1:2-4.
9. The method for preparing a heat-resistant ceramic mud free of lithium minerals according to claim 1, characterized in that: Alumina, titanium dioxide, quartz, potassium feldspar and magnesium oxide all passed through a 100-250 mesh standard sieve.
10. A heat-resistant ceramic mud free of lithium minerals, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium-free heat-resistant domestic ceramic and preparation method thereof
CN113321487A
Lithium mineral-free low-thermal-expansion domestic ceramic and preparation method thereof
CN113336534A
Light fireproof plate based on calcium silicate and preparation method thereof
CN118184272A